2008
DOI: 10.1007/s00330-008-0979-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance of FDG-PET/CT for diagnosis of recurrent uterine cervical cancer

Abstract: The purpose is to evaluate the accuracy of integrated FDG-PET/CT, compared with PET alone, for diagnosis of suspected recurrence of uterine cervical cancer. Fifty-two women who had undergone treatment for histopathologically proven cervical cancer received PET/CT with suspected recurrence. PET-alone and integrated PET/CT images were evaluated by two different experienced radiologists by consensus for each investigation. A final diagnosis was confirmed by histopathology, radiological imaging, and clinical follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 19 publications
0
37
0
1
Order By: Relevance
“…In other studies, sensitivities between 86 and 100%, specificities between 60 and 94%, and accuracies between 70 and 97% were reported [18][19][20][21][22]. As for the efficacy of PET/CT, the study by Chung et al reported a sensitivity of 90.3%, a specificity of 81%, and an accuracy of 86.5% [23], and in the study by Kitajima et al, PET/CT scored a sensitivity of 92%, a specificity of 93%, and an accuracy of 92% [24]. PET/CT also performed well in the present study, with a sensitivity of 97.3%, a specificity of 71.4%, a positive predictive value of 90%, a negative predictive value of 90.9%, and an accuracy of 90.2%.…”
Section: Discussionmentioning
confidence: 94%
“…In other studies, sensitivities between 86 and 100%, specificities between 60 and 94%, and accuracies between 70 and 97% were reported [18][19][20][21][22]. As for the efficacy of PET/CT, the study by Chung et al reported a sensitivity of 90.3%, a specificity of 81%, and an accuracy of 86.5% [23], and in the study by Kitajima et al, PET/CT scored a sensitivity of 92%, a specificity of 93%, and an accuracy of 92% [24]. PET/CT also performed well in the present study, with a sensitivity of 97.3%, a specificity of 71.4%, a positive predictive value of 90%, a negative predictive value of 90.9%, and an accuracy of 90.2%.…”
Section: Discussionmentioning
confidence: 94%
“…The status of the remaining 7 studies was not defined [10, 12, 2023, 31]. Seven studies [13, 22, 2426, 28, 31] enrolled patients in a consecutive manner, including three studies [21, 24, 27] in which the operator was blinded to prior test results. The TP, FN, FP, and TN results, as well as some features of each modality, are shown in Tables II–IV.…”
Section: Resultsmentioning
confidence: 99%
“…When a recurrence of cervical cancer was clinically suspected, 18 F-FDG PET had high accuracy in detecting and staging recurrence and was of major additional value in diagnostic understanding and treatment planning. Furthermore, the use of 18 F-FDG PET/CT (rather than 18 F-FDG PET) in these patients will likely reduce the number of diagnostic tests and help to identify biopsy sites, avoiding interpretation problems due to poor anatomic localization at 18 F-FDG PET alone (13,24).…”
Section: Discussionmentioning
confidence: 99%